(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article studies the corporate governance system in our country, identifies problems and unresolved issues in the field of corporate governance, and, on this basis, studies the scientific research and theoretical and methodological foundations of foreign and local scientists in accordance with modern international standards to develop a national corporate governance system.